PENGARUH LEVERAGE, TIPE INDUSTRI, UKURAN PERUSAHAAN DAN PROFITABILITAS TERHADAP CORPORATE SOCIAL RESPONSIBILITY (CSR) (Studi pada Perusahaan-Perusahaan yang Terdaftar di Bursa Efek Indonesia Periode Tahun 2010-2012) - Permatasari, Hesti Dyah; Prasetiono, Prasetiono (Diponegoro Journal of Management, 2015)
This research aim is to analyze the effect of leverage, industry type, firm size, and profitability to Corporate Social Responsibility Disclosure. This study examined the companies listed on Indonesia Stock Exchange during 2010-2012 periods. The sample was 34 companies which always doing corporate social responsibility disclosure during the research period. The data used are secondary data retrieved by the method of documentation. The analytical method used on this research is multiple regression analysis, hypothesis testing by the determinant coefficient, F-test and T-test. The result on this research showing that leverage, industry type, firm size, and profitability have significant influence to Corporate Social Responsibility Disclosure.